Basic Leadership Training for Karang Taruna Lengau Seprang Village - Ella Silvana Ginting; Tya Wildana Hapsari Lubis; Suci Pertiwi (TRIDARMA: Pengabdian Kepada Masyarakat (PkM), 2021)
Karang Taruna is a community social organization as a forum and means where young people can work to create social welfare, especially for the community around where they live. In the era of modernization as it is today, the mindset of the younger generation has begun to decrease to participate in community organizations such as Karang Taruna, especially among young genrasi in the countryside and villages where the younger generation is less concerned about community activities in their villages but not with the younger generation in Lengau Seprang village of Tanjung Morawa District. In recent years, the younger generation in Lengau Seprang village actively participated in the Karang Taruna organization named Tunas Kencana. But because of the lack of experience and knowledge of the younger generation in the organization, especially knowledge about the basics of leadership and lack of support from the surrounding environment also affect the activities of the younger generation in the village. For this reason, a training was given on the basis of leadership for the members of Karang Taruna Tunas Kencana lengau Seprang village. With this basic leadership training, it is expected to help the problems faced by the younger generation that will be useful for them in running the Karang Taruna organization so as to improve the welfare of the community in Lengau Seprang village. The result achieved is a positive response from the younger generation, as well as village head Lengau Seprang who hopes that later training activities like this will often be done in their villages. The conclusion with this basic leadership training is to provide knowledge about the basis in leadership and the science of skills in organizing.